2018
DOI: 10.3390/agriculture8070103
|View full text |Cite
|
Sign up to set email alerts
|

Relay Intercropping with Cover Crops Improved Autumn Forage Potential of Sweet Maize Stover

Abstract: Maize (Zea mays L.) stover is used globally as winter feed for livestock but the nutritive value is low, requiring supplementation. A 2-year randomized complete block study with three replicates at New Mexico State University's Alcalde Sustainable Agriculture Science Center compared sweet maize (Zea mays var. rugosa; maize-alone) with sweet maize relay intercropped with oat (Avena sativa L.; maize-oat) or turnip (Brassica rapa L.; maize-turnip). Relay intercropping had no effect (p > 0.05) on sweet maize stove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 34 publications
(130 reference statements)
3
18
0
Order By: Relevance
“…Although maize harvested for grain does not provide a large enough window for fall grazing, interseeding of cover crops into standing maize to increase the nutritional value of maize stover can be an alternative establishment method. Interseeding turnips (Brassica rapa L.) into standing maize has been shown to increase in vitro dry matter digestibility (IVDMD) of sweet maize stover and increased ADG [55]. Similarly, Villalobos and Brummer [56] reported that interseeded cover crops at V6 growth stage in irrigated maize increased crude protein content and fiber digestibility for the maize stalks-cover crop mixture in the fall compared with maize stalks alone.…”
Section: Interseeded Annual Forages Into Maize To Improve Grazing Value Of Maize Stovermentioning
confidence: 99%
“…Although maize harvested for grain does not provide a large enough window for fall grazing, interseeding of cover crops into standing maize to increase the nutritional value of maize stover can be an alternative establishment method. Interseeding turnips (Brassica rapa L.) into standing maize has been shown to increase in vitro dry matter digestibility (IVDMD) of sweet maize stover and increased ADG [55]. Similarly, Villalobos and Brummer [56] reported that interseeded cover crops at V6 growth stage in irrigated maize increased crude protein content and fiber digestibility for the maize stalks-cover crop mixture in the fall compared with maize stalks alone.…”
Section: Interseeded Annual Forages Into Maize To Improve Grazing Value Of Maize Stovermentioning
confidence: 99%
“…The site and general methods for this study were previously described in Lauriault et al [ 17 ], using different experimental units within the same randomization. In the present study, the trials with relay intercropping treatments (sweet maize overseeded with rye (maize–rye) and sweet maize overseeded with hairy vetch (maize–vetch)) were conducted in three years at New Mexico State University’s Alcalde Sustainable Agriculture Science Center (36.08° N, 106.05° W, elev.…”
Section: Methodsmentioning
confidence: 99%
“…Winter cereal forages are used widely in the irrigated western USA and other semiarid regions of the world for supplemental autumn and winter forage, and are especially beneficial to provide pasture high in nutritive value for recently weaned calves [ 3 , 16 ]. Lauriault et al (2018) [ 17 ] reported that newly weaned beef cattle grazing sweet maize stover overseeded with oat ( Avena sativa L.) or turnip ( Brassica rapa L.) in the autumn had increased average daily gains (ADG), compared to those grazing sweet maize stover only. Butler et al [ 18 ] reported a similar performance by cattle grazing rye-annual ryegrass ( Lolium multiflorum Lam.)…”
Section: Introductionmentioning
confidence: 99%
“…Covering species, especially grasses, play an important role in the search for technical and economic viability of NT in different regions of Brazil, especially in tropical regions, due to the difficulty of production in the off-season and the rapid decomposition of the accumulated biomass [5,6], leaving the soil unprotected [7]. Intercropping of perennial forages with maize is an alternative for establishing ground cover crops, with the objective of producing maize and soybean grains in NT, keeping the soil permanently covered [8][9][10]. In addition to the high production and persistence of straw, perennial forages have been considered to improve the soil environment.…”
Section: Introductionmentioning
confidence: 99%